2007
DOI: 10.1097/01.sla.0000251708.70219.d2
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Economic Validation of the International Study Group of Pancreatic Fistula (ISGPF) Classification Scheme

Abstract: Biochemical evidence of pancreatic fistula alone has no clinical consequence and does not result in increased resource utilization. Increasing fistula grades have negative clinical and economic impacts on patients and their healthcare resources. These findings validate the ISGPF classification scheme for pancreatic fistula.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
294
1
8

Year Published

2008
2008
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 347 publications
(315 citation statements)
references
References 20 publications
12
294
1
8
Order By: Relevance
“…Nevertheless, the incidences were comparable to the overall incidences of the previous reports using these definitions [1,3,6,7,12,13,22,29] , or were even lower than those in cases restricted to the soft pancreas [9,10] . In a current objective definition by the ISGPF classification scheme, Pratt et al [35] reported an overall incidence of 11.9% in Grade B fistula and 3.4% in Grade C fistula, which were comparable with our results of 14.4% in Grade B fistula and 1.6% in Grade C fistula. A subgroup analysis of the incidences of pancreatic fistula limited to the soft pancreas in each Grade according to the ISGPF definition has not yet been reported to date.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…Nevertheless, the incidences were comparable to the overall incidences of the previous reports using these definitions [1,3,6,7,12,13,22,29] , or were even lower than those in cases restricted to the soft pancreas [9,10] . In a current objective definition by the ISGPF classification scheme, Pratt et al [35] reported an overall incidence of 11.9% in Grade B fistula and 3.4% in Grade C fistula, which were comparable with our results of 14.4% in Grade B fistula and 1.6% in Grade C fistula. A subgroup analysis of the incidences of pancreatic fistula limited to the soft pancreas in each Grade according to the ISGPF definition has not yet been reported to date.…”
Section: Discussionsupporting
confidence: 82%
“…They found the incidence of pancreatic fistula to range from 9.9% to 28.5% according to the different definitions applied. Pratt et al [35] also reported incidences of pancreatic fistula between 9.1% and 19.3% by applying different definitions to 176 patients undergoing a pancreaticoduodenectomy. As a result, it is quite important to use a universally accepted definition of pancreatic fistula to compare the different aspects of the new surgical method with the conventional one.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, postoperative pancreatic fistula (POPF) is still regarded as the most relevant complication after resective pancreatic surgery (distal pancreatectomy and pancreatoduodenectomy) because it potentially leads to deleterious secondary complications, increased health care costs, and prolonged hospital stay [1,2].…”
Section: Introductionmentioning
confidence: 99%